Social Job Stressors can Foster Employee Well-Being: Introducing the Concept of Social Challenge Stressors - Marcel Kern; Clara Heissler; Dieter Zapf (Journal of Business and Psychology, 2020)
Existing social stressor concepts disregard the variety of task-related situations at work that require skillful social behavior to maintain good social relationships while achieving certain task goals. In this article, we challenge the view that social stressors at work are solely dysfunctional aspects evoking employee ill health. Drawing from the challenge-hindrance stressor framework, we introduce the concept of social challenge stressors as a job characteristic and examine their relationships with individual well-and ill-being. In study 1, we developed a new scale for the measurement of social challenge stressors and tested the validity of the scale. Results from two independent samples indicated support for a single-factor structure and showed that social challenge stressors are distinct from related stressor concepts. Using two samples, one of which was already used to test the factor structure, we analyzed the unique contribution of social challenge stressors in predicting employee well- and ill-being. As expected, social challenge stressors were simultaneously related to psychological strain and well-being. Using time-lagged data, study 2 investigated mechanisms that may explain how social challenge stressors are linked to well-being and strain. In line with the stress-as-offense-to-self approach, we expected indirect relationships via self-esteem. Additionally, social support was expected to moderate the relationships between social stressors and self-esteem. Whereas the indirect relationships were mostly confirmed, we found no support for the buffering role of social support in the social hindrance stressors-self-esteem link. Although we found a moderation effect for social challenge stressors, results indicated a compensation model that conflicted with expectations.
Keywords: 650; Challenge and hindrance stressors; Social stressors; Conflicts; Organizational injustice; Employee well-being; Self-esteem; Social support